Transcription CD-ROM - Diane M. Gilmore (South-western Educational Pub., 2007)
Legal office projects is designed to utilize a project-based approach to completing legal office activities that involve legal document preparation, layout, formatting, Internet research, and transcribing. The setting for the projects is a law firm where the student serves as a floating legal assistant for a number of diverse individuals practicing various types of law. The projects allow a hands-on approach to legal document preparation